Forensic Interview of Sexually Abused Children: The Case of Three Selected Child Protection and Investigation Units in Addis Ababa - Tensae Gebrekrstos Gebreegziabher (International Journal of Management, Entrepreneurship, Social Science and Humanities, 2020)
This study examines the application of forensic interview methods used in police investigations to gather evidence from sexually abused children. The investigating police officers need a range of skills related to interviewing victims, helpful in the course of detecting suspects. An effective interview is therefore a milestone to the investigating officers, plan a new way of eliciting relevant information from additional sources. Typically, interviewing requires the police to attempt to identify the type of sex crime considering the phases of pre, present, and post crime acts. The study used a qualitative method to explore the opinions of informants in depth. Seventeen participants were drawn from seven investigating police officers, three public prosecutors, three social workers, and four administrators selected using a purposive sampling technique. Data pertinent to the study were gathered using unstructured and key-informant interview techniques. Besides, observation and document reviews were employed to complement the data solicited from both sources. Thematic analysis was applied to give a thick description of data opinionated by informants. The study shows that investigating police officers are poorly acquainted with the interview techniques established by the Federal Supreme Court Interview Techniques Guideline. The guideline explicitly advocates the police officers' use of free narrative open-ended questions implying ample room to the child to describe the situation of the abuse in his/her own words. The study conveys the message that the police officers should take a series of training on forensic interviews and design the landscape where regular feedback, supervision, and stress management mechanisms will regularly be exchanged.